Encyclopedia > Normalizer

  Article Content

Centralizer and normalizer

Redirected from Normalizer

In group theory, the centralizer and normalizer of a subset S of a group G are subgroups of G which have a restricted action on the elements of S and S as a whole, respectively. These subgroups provide insight into the structure of G.


The centralizer of an element a of a group G (written as CG(a)) is the set of elements of G which commute with a; in other words, CG(a) = {x in G : xa = ax}. If H is a subgroup of G, then CH(a) = CG(a) ∩ H. If there is no danger of ambiguity, we can write CG(a) as C(a).

More generally, let S be any subset of G (not necessarily a subgroup). Then the centralizer of S in G is defined as C(S) = (x in G : for all s in S, xs = sx}. If S = {a}, then C(S) = C(a).

C(S) is a subgroup of G; since if x, y are in C(S), then xy -1s = xsy -1 = sxy -1.

The center of a group G is CG(G), usually written as Z(G). The center of a group is both normal and abelian and has many other important properties as well. We can think of the centralizer of a as the largest (in the sense of inclusion) subgroup H of G having having a in its center, Z(H).

A releated concept is that of the normalizer of S in G, written as NG(S) or just N(S). The normalizer is defined as N(S) = {x in G : xS = Sx}. Again, N(S) can easily be seen to be a subgroup of G. The normalizer gets it name from the fact that if we let <S> be the subgroup generated by S, then N(S) is the largest subgroup of G having <S> as a normal subgroup (compare this with the conjugate closure of S).


If G is an abelian group, then the centralizer or normalizer of any subset of G is all of G; in particular, a group is abelian if and only if Z(G) = G.

If a and b are any elements of G, then a is in C(b) if and only if b is in C(a), which happens if and only if a and b commute. If S = {a} then N(S) = C(S) = C(a).

C(S) is always a normal subgroup of N(S): If c is in C(S) and n is in N(S), we have to show that n -1cn is in C(S). To that end, pick s in S and let t = nsn -1. Then t is in S, so therefore ct = tc. Then note that ns = tn; and n -1t = sn -1. So

(n -1cn)s = (n -1c)tn = (n -1(tc)n = (sn -1)cn = s(n -1cn)
which is what we needed.

If H is a subgroup of G, then the N/C Theorem states that the factor group N(H)/C(H) is isomorphic to a subgroup of Aut(H), the automorphism group of H.

Since NG(G) = G, the N/C Theorem also implies that G/Z(G) is isomorphic to Inn(G), the subgroup of Aut(G) consisting of all inner automorphisms of G.

If we define a group homomorphism T : G → Inn(G) by T(x)(g) = Tx(g) = xgx -1, then we can describe N(S) and C(S) in terms of the group action of Inn(G) on G: the stabilizer of S in Inn(G) is T(N(S)), and the subgroup of Inn(G) fixing S is T(C(S)).

All Wikipedia text is available under the terms of the GNU Free Documentation License

  Search Encyclopedia

Search over one million articles, find something about almost anything!
  Featured Article
French resistance

... in preparation to fight again. Others were former socialists and communists who had fled Gestapo. Many of them hid in the forested regions, especially in th ...

This page was created in 23.8 ms